2020
DOI: 10.1021/acs.jafc.0c00515
|View full text |Cite
|
Sign up to set email alerts
|

Isorhapontigenin Improves Diabetes in Mice via Regulating the Activity and Stability of PPARγ in Adipocytes

Abstract: Isorhapontigenin is a natural bioactive stilbene isolated from various plants and fruits. It has been reported to exhibit several physiological activities including anticancer and anti-inflammation activity in vitro and in experimental animal models. This study aimed to investigate whether isorhapontigenin exerts antidiabetic effects in vivo. To this end, diabetic db/db mice were treated with either 25 mg kg–1 of isorhapontigenin or vehicle intraperitoneally for a period of 5 weeks. The results show that isorh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Isorhapontigenin is a natural derivative of stilbene, which is present in numerous plant species. It has prominent anti-inflammatory, anti-cancer, and anti-diabetic potential [38][39][40]. As a resveratrol analog, isorhapontigenin is a tetrahydroxylated stilbenoid with a methoxy group.…”
Section: Discussionmentioning
confidence: 99%
“…Isorhapontigenin is a natural derivative of stilbene, which is present in numerous plant species. It has prominent anti-inflammatory, anti-cancer, and anti-diabetic potential [38][39][40]. As a resveratrol analog, isorhapontigenin is a tetrahydroxylated stilbenoid with a methoxy group.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ISO exerts the anti-diabetic activity confirmed by in vivo study [26]. ISO treatment among mice at the dose of 25 mg/kg b.w.…”
Section: Isorhapontigenin-successor Of Resveratrolmentioning
confidence: 73%
“…As a result, changes in adipose tissue reduction were observed, and adipose insulin sensitivity was also improved. What is more, the mRNA expression levels of PPARγ (peroxisome proliferator-activator receptor gamma) were higher in white adipose tissue among mice treated by ISO comparing to the control group [26].…”
Section: Isorhapontigenin-successor Of Resveratrolmentioning
confidence: 93%
See 1 more Smart Citation
“…In total, four promising candidates including hesperidin, isorhapontigenin, salmeterol, and gallocatechin-7-gallate were demonstrated to show inhibitory activity on SARS-CoV-2 virus-infected Vero cells. As presented in Figure 7 , hesperidin (a flavanone glycoside isolated from various citrus fruits, such as orange; Küçükler et al, 2021 ) restrained the growth of the SARS-CoV-2 virus with an EC 50 value of 1.25 μg/ml ( Figure 7B ) while isorhapontigenin (originated from plants and fruits, such as Chinese herb Gnetum cleistostachyum; Chu et al, 2020 ) inhibited the replication of virus with an EC 50 value of 0.3 μg/ml ( Figure 7C ). As a citrus bioflavonoid, hesperidin possesses a variety of biological activities such as antioxidant, anti-inflammatory, and antivirus properties ( Ding et al, 2018 ; Afzal et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%